Minimally Invasive Aesthetic Procedures: An Update on a Decade-Old Prediction - Moayer, Roxana; Sand, Jordan P.; Nabili, Vishad; Keller, Gregory S. (Facial Plastic Surgery, 2017)
In 2007, the senior author (G.S.K.) published a commentary on the importance of incorporating minimally invasive aesthetic procedures into facial plastic surgery practices and training programs. The now decade-old prediction suggested that failing to perform minimally invasive aesthetic procedures placed facial plastic surgeons at risk of practice “phase out.” By not providing the most current options that patients' desire, we may lose patients to outside providers willing to perform those procedures. The aim of this article is to provide an update on this perspective by putting forth the results of the most up-to-date data on practice patterns with regard to minimally invasive aesthetic procedures.
Keywords: minimally invasive; cosmetics; facial plastic surgery